1997
DOI: 10.3109/01674829709085566
|View full text |Cite
|
Sign up to set email alerts
|

Physical complaints and emotional stress related to routine diagnostic procedures of the fertility investigation

Abstract: The aim of this study was to map out the extent of the physical complaints and emotional stress due to diagnostic routines of the infertility work-up. To this end a questionnaire was sent to 96 consecutive couples visiting an infertility clinic of a university hospital. The results indicate that women often have physical complaints as a result of the hysterosalpingography (59%) and the diagnostic laparoscopy (47%) and mostly experience these diagnostic procedures as very stressful. Both the postcoital test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Previous reports have noted that the level of anxiety and distress experienced by patients correlates with the level of invasiveness of the procedure . In addition, baseline anxiety before the procedure has a significant effect on perceived pain during and after the procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Previous reports have noted that the level of anxiety and distress experienced by patients correlates with the level of invasiveness of the procedure . In addition, baseline anxiety before the procedure has a significant effect on perceived pain during and after the procedure.…”
Section: Discussionmentioning
confidence: 94%
“…[ 8 ] The pain experienced during and after HSG can have a negative impact on the woman's ability to cooperate with the procedure, thus limiting the usefulness of this investigation, as well as negatively influencing the woman's willingness to undertake similar diagnostic studies. [ 9 ] Different techniques have been used in attempts to make the procedure less painful including the use of balloon catheters rather than metal cannulas. [ 10 ] Furthermore, there are so many studies comparing different analgesics for pain relief during HSG, but so far there appears to be no consensus in terms of type, route, and timing of analgesia to be administered.…”
Section: Introductionmentioning
confidence: 99%
“…3 It is reported that HSG was a more stressful procedure for women than a mammography or abdominal ultrasonography. 4 Conflicts of interest: The authors declare that there are no conflicts of interest related to the subject matter or materials discussed in this article. Patient comfort and pain perception directly affects the ability to safely complete a procedure.…”
Section: Introductionmentioning
confidence: 99%